Anxiety levels and related symptoms in emergency nursing personnel in Greece - Stathopoulou, Hariklia; Panagiotopoulou, Fotini; Papathanassoglou, Elizabeth; Karanikola, Maria (My University, 2011)
Introduction: Several studies provide evidence for the association between work stress and mild psychiatric morbidity among emergency nurses. These symptoms have not been explored in Greek nursing personnel employed in emergency departments. The aim of this descriptive correlational study was to investigate the presence of anxiety and stress symptoms among emergency nursing personnel in Greece. Methods: The sample was composed of nursing personnel employed in emergency departments of 8 adult General hospitals in Greece (N = 213). The Hamilton Anxiety Scale was applied for the quantitative assessment of anxiety symptoms, along with demographic, vocational, and educational data. Descriptive statistics were explored, and nonparametric comparisons, as well as correlational tests, were performed. Results: Anxiety levels were found to be mild (1.102 ± 0.53), with women (P = .021, Mann-Whitney U test) and nursing personnel employed in public sector hospitals (P = .029, MannWhitney U test) having higher anxiety level scores. In addition, a statistically significant mild correlation was observed between work experience in the emergency department and anxiety states (τ = 0.178, P = .011). The most commonly reported manifestations of mild psychiatric symptomatology were sleep disturbances (2.32 ± 1.2), anxious mood (1.57 ± 1.1), and depressed mood (2.38 ± 1.2), with 24.8% of the participants reporting very severe sleep disturbance, 23.9% reporting very severe depressive mood, and 10.7% reporting very severe anxious mood. Discussion: Hospital administrators need to be aware of the extent of workplace stress and subsequent anxiety symptoms that exist in emergency nurses. Staff counseling, continuing professional education, and empowerment strategies may need to be implemented to prevent psychiatric morbidity, as well as job dissatisfaction and resignations.
Keywords: Mild psychiatric symptoms; Anxiety; Burnout; Emergency nurses